Hubungan Antara Pengetahuan, Pendapatan, Dan Pekerjaan Ibu Dengan Kehamilan Risiko Tinggi Di Puskesmas Kecamatan Denpasar Barat Tahun 2018 - Wilda Fitrianingsih; Ni Nyoman Suindri; Ni Wayan Armini (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
High risk pregnancy is one of causes which can increase the Maternal Mortality Rate (MMR) nationally and regionally. The number of MMR in Denpasar City is 54/100.000 in 2015 and 2016. Primary health center in Denpasar Barat district has the biggest number of high risk pregnancy in Denpasar. The objectives of this research were to know the association between knowledge, income, and occupation to high risk pregnancy in primary health center of Denpasar Barat district. This observational research used cross sectional design which conducted from April to June 2018 with consecutive sampling technique. Sample used 55 pregnant women who were visited to primary health center. 22 women in Puskesmas I and 33 women in Puskesmas II. Data collected by questionnaire and high risk pregnancy accounting system by Poedji Rochjati Score. Data analysis used univariate with frequency distribution and bivariate with Chi Square test based on significance level p 0,05. The result showed there were significant associations between knowledge (p = 0,01), income (p = 0,01), and occupation (p = 0,011) to high risk pregnancy. Pregnant women with the less knowledge, low income, and work active had 4,2 times to get high risk pregnancy. Pregnant women expected to apply healthy pregnancy to reduce high risk pregnancy, health workers expected to improve antenatal care, and also researchers expected adding other variables which affect the high risk pregnancy.